Pengaruh Kualitas Produk, Promosi, dan Citra Merek Terhadap Keputusan Pembelian Wafer Nabati Di Tip-top Rawamangun - Dinda Nabila; Hariadi Hadi Suwarno (LPPM Universitas Asa Indonesia, 2022)
The purpose of this research to determine and analyze the effect of product quality, promotion, and brand image on purchasing decisions of Nabati Wafers at Tip-top Rawamangun. The population in this study was 100 respondents with data collection using a questionnaire given to respondents with accidental sampling technique. The analytical method used in this research is multiple regression analysis. The results of this study indicate that product quality variables, promotion variables, and brand image variables simultaneously affect the purchasing decision of Nabati Wafers at Tip-top Rawamangun. Then the results partially show that product quality and brand image variables have a significant effect on purchasing decisions, while promotion variables have no effect on purchasing decisions.